Rapid Molecular Response to Dasatinib in a Pediatric Relapsed Acute Lymphoblastic Leukemia With NCOR1-LYN Fusion - Dai, Hai-Ping; Yin, Jia; Li, Zheng; Yang, Chun-Xiao; Cao, Tin; Chen, Ping; Zong, Yun-Hui; Zhu, Ming-Qing; Zhu, Xia-Ming; Xiao, Sheng; Wu, De-Pei; Tang, Xiao-Wen (Frontiers in Oncology, 2020)
Background: Philadelphia chromosome-like acute lymphoblastic leukemia (Ph-like ALL) is associated with high rates of treatment failure and poor outcome. Activation of ABL/Src family kinases is found in approximately 10% of Ph-like ALL, which can be therapeutically targeted by tyrosine kinase inhibitors. LYN is a member of the ABL/Src-tyrosine kinase family. Somatic LYN rearrangements are found in 5 cases of hematopoietic malignancies so far, although none of them were treated with tyrosine kinase inhibitors. Case presentation: a 6-year-old boy with relapsed B-ALL had no response to reinduction chemotherapy. He was then treated with the ABL1 tyrosine kinase inhibitor dasatinib and achieved complete remission within 2 weeks. Haploidentical allogenic stem cell transplantation (allo-HSCT) was subsequently performed and maintenance therapy with dasatinib initiated 8 weeks post-transplantation. He has been in minimal residual disease negative remission for 10 months after allo-HSCT. Result: His bone marrow karyotype showed a balanced translocation between chromosomes 8 and 17, leading to a NCOR1-LYN fusion gene confirmed with sequencing. Conclusion: Although LYN overexpression is described in many AML and B-ALL patients, intragenic LYN rearrangement is a rare event. For the first time, we present evidence that dasatinib is effective in treating a pediatric B-ALL with NCOR-LYN fusion.